Harmonic components of leakage current as a diagnostic tool to study the aging of insulators - Ahmad, Hussein (Elsevier B.V., 2008)
This paper presents a harmonic component monitoring technique to study the aging of toughened glass insulators. Harmonic analysis theories and the principles of statistical analysis are applied in this finding. Both new and aged insulators are tested for harmonic components with a 240Vrms AC voltage input. The power spectrum obtained from experiment is analyzed for the potential harmonic component as an indicator of aging in toughened glass insulators. The new and aged toughened glass insulators' power spectrums are compared to obtain the desired result. The level of confidence for the obtained result is determined by using statistical analysis. It is found that the fundamental, third, fifth and seventh harmonic components have positive results (i.e. the power consumed by these harmonic components increases with the age of the toughened glass insulator). The experimental results show that the third harmonic component is an indicator of the aging of toughened glass insulators.